Pembuatan Video Animasi oleh Guru-Guru MI Muhammadiyah 09 Labuhan sebagai Solusi Pembelajaran Matematika di Masa Pandemi Covid-19 - Himmatul Mursyidah (Jurnal Pengabdian Kepada Masyarakat (ABDIMAS) Universitas Baturaja, 2025)
Teachers of MI Muhammadiyah 09 Labuhan have problems in the mathematics learning process before and during the Covid-19 pandemic. They are teachers have not used learning media that support online learning, student interest in learning mathematics is low, and mathematics learning outcomes is not optimal. The causes of this problem are teachers often use the assignment method and the media used have not been able to attract students' interest in learning. Therefore, a service program was carried out in a training series on making mathematics learning media i.e. animated videos which included making storylines, creating animated characters, making animated videos, animated characters dubbing, uploading animated videos to YouTube, and implementing them to students. The service program can make teachers more creative in making learning media, they are able to use several computer applications and manage YouTube channels. In addition, students feel happy and interested in the mathematics learning process.